The problem of Development of Conflictological Competence of Future Officers. (Journal of Educational Sciences, 2016)
The research efforts of the authors focus on issues to improve the effectiveness of management processes, resolve problems in the course of professional interaction between superiors and subordinates, positive regulation of intra-group interpersonal relationships and increase professionalism in the work of the managerial staff. Practice the service and combat activity shows that it is impossible, relying only on the legislative and administrative principles to improve the quality of management units. A military staff is a living organism, existing in some laws and regulations, part not stated in the academic literature. Leaders do not have sufficient administrative and life experience, experience serious difficulties in the process of building relationships with subordinates, especially with contract military personnel, serving in positions of privates and sergeants.
Keywords: conflictological competence; professional competence; managerial activities; technology; problem – design approach